Modal Sosial dalam Pengelolaan BUMG di Gampong Trieng Gadeng Aceh Timur - Zulfadhli Zulfadhli; Khairulyadi Khairulyadi (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2021)
Social capital can be one of the factors or forces that support the empowerment process in the community. This article aims to describe the role and elements of forming social capital in the management of BUMG in Trieng Gadeng Village, Darul Aman District, East Aceh. The qualitative method used and data obtained from observations, interviews, and literature studies. The results of this study indicate that the types of social capital in the management of BUMG are bounding and linking. Geuchik as an actor, support both types of social capital. Geuchik's leadership can make the elements of social capital work effectively, such as building trust between various parties, running the BUMG program following local norms, and building social networks. So, the social capital plays a role as a driving force for the birth of cooperation between the government, BUMG managers, and the community in the success of the program set by BUMG in Trieng Gadeng Village, South Aceh.